PERTANGGUNGJAWABAN PIDANA PADA PELAKU TINDAK PIDANA PENIPUAN JUAL BELI ONLIN - Putra, Ida Bagus Dwi Parama; Pratama Sukma, Putu Angga (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
E-commerce is a process of buying and selling transactions which in practice are carried out online via electronic media. The buying and selling process no longer requires face-to-face meetings and the transaction process is carried out online. This has led to an increase in cases of online fraud. This research aims to determine the regulations and criminal responsibility for perpetrators of online buying and selling crimes. This paper uses a normative research method using a statutory approach, a conceptual approach. The results of this research show that regulations regarding criminal acts of fraud are generally regulated in Article 378 of the Criminal Code, and to strengthen the legal basis they can be accommodated through Article 28 paragraph (1) of the ITE Law. Criminal liability for perpetrators of online buying and selling fraud must fulfill the elements of each article, namely Article 378 of the Criminal Code and Article 28 paragraph (1) of the ITE Law and the imposition of responsibility in Article 28 paragraph (1) of the ITE Law which explains losses in the case of buying and selling. in the online world